Bainite formation kinetics in steels and the dynamic nature of the autocatalytic nucleation process. (November 2017) - Ravi, Ashwath M.; Sietsma, Jilt; Santofimia, Maria J.
Abstract: Over the years, a quantitative theory to explain bainite formation kinetics has been proposed based on the nucleation kinetics of bainitic sub-units. Although the theory shows acceptable correlation with experimental results, it is observed that the kinetic models show a certain degree of discrepancy with actual kinetics. It is identified that these mainly arise due to the inadequate estimation of autocatalytic nucleation, especially as a function of progress of bainite formation. With the help of this observation, the kinetic model is modified and a better insight into the process of autocatalytic nucleation, essential in bainite formation, is obtained. Graphical Abstract: